Helicons in plasma solid-state waveguide of cylindrical configuration - Averkov, Yu.O.; Prokopenko, Yu.V.; Yakovenko, V.M. (Вопросы атомной науки и техники, 2019)
The theory of electromagnetic eigenwaves of a cylindrical plasma waveguide located in a constant longitudinal magnetic field has been created. A dispersion equation has been obtained under condition when the ratio of the collision frequency of the majority charge carriers to their cyclotron frequency is substantially less than one. It is shown there are bulk-surface helicons in a plasma waveguide. In the absence of charge-carrier collisions, their propagation is accompanied by a surface current directed parallel to the longitudinal axis of symmetry of the cylinder. Collisions of charged particles destroy the surface current and lead to the formation of additional H-type hybrid waves, the field localizations of which are concentrated near the side surface of the waveguide. The nonreciprocity effect of the eigenwaves, differing in the direction of propagation along the azimuthal coordinate, as well as when the direction of the external magnetic field is changed, has been discovered.